2021
DOI: 10.1017/s1368980021000999
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ultra-processed food consumption during the first Italian lockdown following the COVID-19 pandemic and major correlates: results from two population-based cohorts

Abstract: Objective: To evaluate changes in ultra-processed food (UPF) intake and its major correlates during the first Italian lockdown (March 9 -May 3 2020). Design: Retrospective observational study. Setting: Italy. Participants: We analysed 2,992 subjects (mean age 57.9±15.3 y, 40.4% men). Individual participant data were pooled from 2 retrospective cohorts: 1) The Moli-LOCK cohort consists of 1,501 adults, a portion of the larger Moli-sani Study (n=24,325; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
2
36
0
3
Order By: Relevance
“…Due to pandemic status limitations, with difficulty in performing person-to-person questionnaires or interviews, all of the studies included data collected through online questionnaires or, on a few occasions, through telephone or web interviews ( 22 , 23 , 25 , 31 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to pandemic status limitations, with difficulty in performing person-to-person questionnaires or interviews, all of the studies included data collected through online questionnaires or, on a few occasions, through telephone or web interviews ( 22 , 23 , 25 , 31 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were carried out during the first 3 mo of lockdown (March to May 2020), when containment measures were stricter worldwide. Otherwise, the recruitment period of some surveys lasted until September ( 23 , 25 , 113 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 20 Other study found an increase in sugar drinks and ultra processed food during the pandemic. 21 , 22 Therefore, the objective of the present review is to evaluate the effect of quarantine on dietary habits during enforced lockdowns.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in diet behaviours during the pandemic are associated with several factors including age, gender, body mass index (BMI), physical activity and experiencing a larger psychological impact and larger shifts in lifestyle as a result of lockdown restrictions [4,14,[21][22][23][24][25][26][27]. Given the relationship between a sub-optimal diet and relative risk of cardiovascular disease, cancer and allcause mortality, there could be serious long-term public health consequences if the initial unfavourable changes in dietary behaviours during the pandemic are maintained [28,29].…”
Section: What This Paper Addsmentioning
confidence: 99%